Staining and Embedding of Human Chromosomes for 3-D Serial Block-Face Scanning Electron Microscopy - Mohammed Yusuf; Bo Chen; Teruo Hashimoto; Ana Katrina Estandarte; George Thompson; Ian Robinson (BioTechniques, 2014)
The high-order structure of human chromosomes is an important biological question that is still under investigation. Studies have been done on imaging human mitotic chromosomes using mostly 2-D microscopy methods. To image micron-sized human chromosomes in 3-D, we developed a procedure for preparing samples for serial block-face scanning electron microscopy (SBFSEM). Polyamine chromosomes are first separated using a simple filtration method and then stained with heavy metal. We show that the DNA-specific platinum blue provides higher contrast than osmium tetroxide. A two-step procedure for embedding chromosomes in resin is then used to concentrate the chromosome samples. After stacking the SBFSEM images, a familiar X-shaped chromosome was observed in 3-D.